COORDINATED LOCATION, DISTRIBUTION AND INVENTORY DECISIONS IN SUPPLY CHAIN NETWORK DESIGN: A MULTI-OBJECTIVE APPROACH - Reza Nasiri, G.; Davoudpour, Hamid (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: This research presents an integrated multi-objective distribution model for use in simultaneous strategic and operational food supply chain (SC) planning. The proposed method is adopted to allow use of a performance measurement system that includes conflicting objectives such as distribution costs, customer service level (safety stock holding), resource utilisation, and the total delivery time, with reference to multiple warehouse capacities and uncertain forecast demands. To deal with these objectives and enable the decision makers (DMs) to evaluate a greater number of alternative solutions, three different approaches are implemented in the proposed solution procedure. A detailed case study derived from food industrial data is used to illustrate the preference of the proposed approach. The proposed method yields an efficient solution and an overall degree of DMs